Investigating mitotic vulnerabilities that arise upon oncogenic cell transformation - Shirnekhi, Hazheen K., author; DeLuca, Jennifer G., advisor; Markus, Steven, committee member; Nishimura, Erin, committee member; Bailey, Susan, committee member (Colorado State University. Libraries, 2020)
During mitosis, cells must accurately divide their duplicated chromosomes into two new daughter cells. This process is highly regulated and much of this regulation is centered around kinetochores. Kinetochores are large proteinaceous structures built upon centromeric heterochromatin that must form stable, load-bearing attachments to microtubules (MTs) emanating from the spindle poles. Failure to undergo high-fidelity cell division can result in aneuploidy and even progress to continued mis-segregation in a phenomenon known as chromosome instability (CIN). As aneuploidy results from defective pathways in mitosis, it is important to characterize the changes cancer cells exhibit in their mitotic machinery, with the goal of identifying targets for therapeutic potential. Here, we utilize a human papillomavirus cell culture model system to determine how expression of E6 or E7, two viral transforming proteins, influences mitosis. We find that E6-expressing cells exhibit a weakened spindle assembly checkpoint (SAC) and an increased incidence of pole-associated chromosomes. This combination of mitotic errors allows some of these cells to exit mitosis in the presence of improper kinetochore-MT attachments, leading to aneuploid daughter cells. Defective mitotic processes in cancer cells provide a means of differentiating them from healthy cells, which may be important in developing new effective cancer therapeutics. Through two independent cancer lethality screens, the mitotic proteins BuGZ and BubR1 were identified as essential for Glioblastoma Multiforme cancer cell survival but dispensable for healthy neural cell survival. We characterize the important chaperone-like role BuGZ plays in mitosis to examine its apparent dispensability in healthy cells. BuGZ aids in the kinetochore loading of Bub3, which in turn is needed for the kinetochore loading of proteins with important roles in kinetochore-MT attachment and in spindle assembly checkpoint signaling. BubR1's cancer lethality has also been previously described in Glioblastoma cells. BubR1 is needed to recruit the PP2A phosphatase to kinetochores, where it stabilizes kinetochore-microtubule attachments. We identify the HEC1 tail as a substrate for the BubR1-recruited population of PP2A, and we demonstrate that kinetochore-microtubule attachment defects in BubR1 depleted cells can be rescued with a phospho-null HEC1 mutant. This work identifies important changes in the mitotic machinery of transformed cells, providing potential pathways to target for therapeutics that may apply to many different cancers.